Luminescent properties and energy transfer processes in YAG:Er single crystalline films - Zorenko, Yu.; Gorbenko, V.; Zorenko, T.; Savchyn, V.; Batentschuk, Miroslaw; Osvet, Andres; Brabec, Christoph (Journal of Luminescence, 2014)
The paper is dedicated to studying the optical properties of YAG:Er single crystalline films (SCF) grown by liquid phase epitaxy. The absorption, cathodoluminescence and photoluminescence spectra were measured for the YAG:Er SCFs with different doping levels of Er from 0.735 to 6.6 at%. The luminescence spectra and luminescence excitation spectra under synchrotron radiation excitation in the fundamental absorption range of the YAG and in the intrinsic f-d absorption bands of Er ions reveal the peculiarities of energy transfer from the YAG host to the Er ions. © 2014 Elsevier B.V.
Keywords: Liquid phase epitaxy; Luminescence; Single crystalline films; YAG